What underlies the emergence of stimulus- and domain-specific neural responses? Commentary on Hernandez, Claussenius-Kalman, Ronderos, Castilla-Earls, Sun, Weiss, & Young (2018). (February 2019) - Dick, Frederic; Krishnan, Saloni
Abstract: Hernandez et al (2018) provide a welcome historical perspective and synthesis of emergentist theories over the last decades, particularly in their focus on theoretical differences. Here we discuss a number of neuroimaging findings on the character and drivers of seemingly domain-selective neural response preferences, and how these might bear on the predictiveness of different emergentist accounts. Highlights: There is considerable counter-evidence to claims of higher-level domain- and category-specific neural responses. Neural sensitivity to different stimulus classes is associated with expertise in perceiving and producing those stimuli. Parsimonious emergentist theories will be able to account for such empirical findings.